Integrasi Sistem Informasi Kepuasan Belajar Mengajar Program Studi Teknik Informatika Dengan Sistem Informasi Akademik Unram Menggunakan Web Service - Fitri Bimantoro; Ida Bagus Ketut Widiartha; I Gede Pasek Suta Wijaya; Ario Yudo Husodo (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2019)
One of the tasks of a university is teaching. To keep the quality by improving the teaching qualifications, materials, teaching facilities, and infrastructure. but, one of the important things is to keep the quality of teaching. The quality of teaching can be measured from the feedback of the students. Informatics Department of Mataram University has a system to get feedback from its students called SIKBM (a questioner system for teaching). Unfortunately, not of all the students will fill this questioner because there is no interest for the students. So, we apply a web service system that connects SIKBM and SIA (academic information system). It will force the students to access SIKBM as a requirement to fill KRS (Course selection sheet) on SIA. The result shows that on even semester of 2017, we gain feedback for all of the courses we did not get in the previous years.